Indications of physical beautification for immaterial labor - De Deus, Estefani Sandmann; Grisci, Carmem Ligia Iochins (Revista de Administração da UFSM, 2019)
With the overall objective of questioning whether there is evidence pointing to physical beautification as a positive factor for immaterial labor, the present paper sought specifically to gather evidence from: a) the Brazilian Society of Plastic Surgery (ABCP); b) the Brazilian Association of personal hygiene, perfume and cosmetics industry (ABIHPEC); c) the Brazilian institute of geography and statistics (IBGE); d) the Commercial Board of the State of Rio Grande do Sul (JUCERGS); e) headlines of nationwide circulation magazines. Evidence was found pointing to a relationship between production and consumption of beauty products with a view to self-profitability within the scope of immaterial labor. From the results of the study, it can be said that the previously mentioned evidence strengthens physical attractiveness as a positive factor for immaterial labor. With the overall objective of questioning whether there is evidence pointing to physical beautification as a positive factor for immaterial labor, the present paper sought specifically to gather evidence from: a) the Brazilian Society of Plastic Surgery (ABCP); b) the Brazilian Association of personal hygiene, perfume and cosmetics industry (ABIHPEC); c) the Brazilian institute of geography and statistics (IBGE); d) the Commercial Board of the State of Rio Grande do Sul (JUCERGS); e) headlines of nationwide circulation magazines. Evidence was found pointing to a relationship between production and consumption of beauty products with a view to self-profitability within the scope of immaterial labor. From the results of the study, it can be said that the previously mentioned evidence strengthens physical attractiveness as a positive factor for immaterial labor.